The Effect of Product Knowledge, Price, and Product Design on Batik Banyuwangi Repurchase Intention - Cempaka Paramita; Gusti Ayu Wulandari; Vanya Pinkan Maridelana; Rosa Nuril Safitri; Yuliani Anas Maliki (AIBPM Publisher, 2021)
Batik is one of the most famous arts of Indonesia's cultural heritage, which has thousand of motifs and pattern originating from different regions. Each region has its own Batik motif, including Banyuwangi. Banyuwangi is one of the regents in East Java, Indonesia. Banyuwangi has 21 unique batik motifs that are recognized locally as well as around the world. The objective of this study is to examine the effect of product knowledge, price, and product design on repurchase intention of Batik Banyuwangi. The sample consisted of 114 respondents. This sample was selected using a non-probability sampling method, i.e., purposive sampling. Research data was collected using both online and offline surveys. Multiple linear regression analysis was used to analyze the data. The results show that product knowledge, price, and product design have a significant partial impact on Batik Banyuwangi's repurchase intentions.